Kajian Space Syntax pada Penelitian Kantor BPJS Kesehatan Cabang Utama Bandung - Khuzaimah, Alifah Nuhaa; Hanafiah, Ully Irma Maulina; Faril Nanda, Rexha Septine (Pusat Publikasi Ilmiah, 2024)
ABSTRACTThe BPJS office serves as a place for administrative activities and public services related to social security programs in Indonesia. The BPJS Kesehatan office, specifically, plays a crucial role in providing services related to health insurance and social security. The importance of delivering excellent services is paramount to meet the needs and satisfaction of the public. However, issues regarding the quality of public services in Indonesia have influenced public opinions about the services provided by BPJS. To address these issues, the research employs a space syntax approach to analyze the spatial relationships between adjacent spaces and identify the connectivity of spaces, both direct and indirect. The applied methodology involves surveys and observations, with data being analyzed by referencing previous research. The primary objective of the research is to analyze the spatial configuration, including the elements of interior design, in the BPJS Kesehatan office. The anticipated outcomes of this research are expected to serve as a valuable reference and contribute to further studies by other researchers. By gaining insights into the spatial configuration and interior elements, it is hoped that the research findings will provide a basis for improvements in the quality of public services at BPJS Kesehatan. This research also aims to be a foundation for future investigations in this field.